2021
DOI: 10.2903/j.efsa.2021.6491
|View full text |Cite
|
Sign up to set email alerts
|

The 2019 European Union report on pesticide residues in food

Abstract: Under European Union legislation (Article 32, Regulation ( EC ) No 396/2005), the EFSA provides an annual report which examines pesticide residue levels in foods on the European market. This report is based on data from the official national control activities carried out by EU Member States, Iceland and Norway and includes a subset of data from the EU ‐coordinated control programme which uses a randomised sampling stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 83 publications
0
65
0
7
Order By: Relevance
“…Among the unprocessed plant products analyzed in the framework of the European Union Control Program (EUCP) during the five-year duration of the study [49][50][51][52][53], multiple residues were also reported in citrus samples: in 2014, up to 60.5% (nine different pesticides were detected in an individual orange sample); in 2015, up to 5.6% (seven different compounds were determined in an individual sample of orange juice) and in 2017, up to 58.7% (in two orange samples originating from a third country, up to 12 different active compounds were reported, while in two other samples, which were produced within the EU, 11 pesticide residues were determined in each of them). In all reports, chlorpyrifos was among the most frequently quantified pesticides.…”
Section: Citrus Samples With Multiple Residuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the unprocessed plant products analyzed in the framework of the European Union Control Program (EUCP) during the five-year duration of the study [49][50][51][52][53], multiple residues were also reported in citrus samples: in 2014, up to 60.5% (nine different pesticides were detected in an individual orange sample); in 2015, up to 5.6% (seven different compounds were determined in an individual sample of orange juice) and in 2017, up to 58.7% (in two orange samples originating from a third country, up to 12 different active compounds were reported, while in two other samples, which were produced within the EU, 11 pesticide residues were determined in each of them). In all reports, chlorpyrifos was among the most frequently quantified pesticides.…”
Section: Citrus Samples With Multiple Residuesmentioning
confidence: 99%
“…The citrus fruits of the present study were sampled from citrus trees at various growth (BBCH) stages. However, and especially with respect to chlorpyrifos, which is not authorized in the EU, based on EFSA Annual Reports on pesticide residues in the last five years [49][50][51][52][53], several MRL exceedances for chlorpyrifos in oranges analyzed in the EU have been reported.…”
Section: Citrus Samples With Residues Of Non-authorized Pesticidesmentioning
confidence: 99%
“…Most synthetic pesticides are banned from OF production, but the European Food Safety Authority highlighted that pesticide residues have been quantified in 13.2% of samples of OFs (vs. 45.8% in conventional foods), probably because of external or residual soil contaminations ( 18 ). If the benefits of OFs are potentially due to their lower content of pesticide residues, studying the potential health benefits of OF consumption as compared with conventional food consumption needs special consideration in infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Необходимо уточнить, что понятие «остаточные количества пестицида» включает содержание в продуктах питания, сельскохозяйственном сырье или кормах для животных, помимо самого активного ингредиента, присутствие которого связано с применением пестицида, также токсичных продуктов его метаболических превращений или возможных реакций [1].…”
Section: Introductionunclassified
“…Представленная экспериментальная схема экстракции и дисперсионной сорбционной очистки положена в основу Методических указаний «Многоостаточное определение пестицидов различной химической природы в продукции растениеводства», устанавливающих метод определения остаточных количеств 27 действующих веществ пестицидов (ацетамиприда, имидаклоприда, карбендазима, клотианидина, крезоксим-метила, пенконазола, пираклостробина, пириметанила, спироксамина, тиабендазола, тиаклоприда, тиаметоксама, фенгексамида, цимоксанила, тефлутрина, метрибузина, фенпропиморфа, триадимефона, ципродинила, триадименола, флутриафола, ципроконазола, трифлоксистробина, дифлюфеникана, бифентрина, тебуфенпирада и пирипроксифена) в овощах и фруктах (плоды семечковых и косточковых культур, огурцов, томатов, ягоды винограда, клубни картофеля, корнеплоды свеклы и моркови) 1 .…”
Section: Introductionunclassified